The Dimensional Distribution of Kenaf and Apocynum Fibers. Issue 5 (3rd May 2020) - Liu, Jing; Song, Yan; Han, Guangting; Han, Yuhui; Zhang, Yuanyuan; Jiang, Wei
ABSTRACT: In this research, single fiber cell separation method was studied and optimized. More than 200 fiber cell dimensional sizes of kenaf and apocynum were analyzed. Furthermore, the diameter changes of kenaf fiber cell before and after different degumming treatments were also explored. Results showed that the average length and diameter of kenaf fiber are 2.16 mm and 10.56 μm, while the average length and diameter of apocynum fiber are 9.04 mm and 7.41 μm. It was also found that the average diameter of kenaf and apocynum fibers decreased with the degumming process, and the diameter distribution became more even.